The toxic effect of heavy metals on algal biomass (Spirulina sp.) and carbonic anhydrase activity, an enzyme which is central to algal application in metal precipitation - Nightingale, Leigh (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
Acid rmne drainage (AMD) is a major pollution problem througbout the world, adversely affecting both surface and groundwaters. AMD is principally associated with the mining of sulphide ores. The most commonly associated minerals being sulphur, copper, zinc, silver, gold, lead and uranium. As conventional methods for removing heavy metals from wastewater are often prohibitively expensive, the implementation of biological processes for the removal of heavy metals has become a realistic practice. The objectives of this project was firstly to establish the effect of copper, lead and nickel, heavy metals commonly found in AMD waters, on the enzyme carbonic anhydrase, which is an integral part of the carbon concentrating mechanism (CCM) and secondly, to determine the feasibility of using the alkalinity generated by Spindina for the precipitation of heavy metals from solution. Initially, batch flask experiments were performed and it was found that the algae were able to utilise the bicarbonate supplied in the medium, under CO, limiting conditions, through the induction of their CCM, resulting in the generation of carbonate. The effect of the inhibitors, acetazolamide (AZ) and ethoxyzolamide (EZ), were also investigated in order to determine the importance of carbonic anhydrase (CA) in inorganic carbon accumulation and photosynthesis. Results obtained were consistent with those observed in literature and it was found that at IOOf.LM AZ and EZ, complete inhibition of photosynthesis and carbonic anhydrase occurred, with no oxygen being evolved. The results obtained from the inhibitor experiments substantiate the findings that carbonic anhydrase is an important part of the CCM, and that the dehydration of bicarbonate to carbon dioxide and hydroxide ions, is in fact an enzymatic process regulated by the enzyme carbonic anhydrase and is essential for efficient photosynthesis. The effect of heavy metals on Spirulina was also investigated. Lead, copper and nickel were all found to cause a reduction in the synthesis of chlorophyll a, which resulted in a decrease in photosynthetic efficiency and eventually death of the culture. The morphology of the algae was also severely affected by heavy metals, with degradation and aJmost complete disintegration of the algal filaments occurring. Using the Wilbur-Anderson assay method, carbonic anhydrase activity was found to be lower in the experimental flasks containing heavy metals, than the control flasks, reducing the algae's ability to utilise the bicarbonate in solution for effective photosynthesis. The Wilbur-Anderson assay method did not prove to be a reliable method for measuring changes in enzyme activity as results were found to be erratic. Therefore attempts were made to use an oxygen electrode as an alternative method for determining the effects of various parameters on enzyme activity and photosynthesis, this proved to be more successful. Because of the toxic effects of heavy metals on Spirulina it was decided that the use of the biogenic alkalinity generated by the algae for the precipitation of heavy metals may be successfully employed as an alternative method for bioremediation and metal recovery. Carbonate reacts readily with metals, therefore the carbonate produced by this algal system was used for the precipitation of metals. It was possible to categorise the precipitation reactions observed into three groups, namely those metals which, a) precipitate as hydroxides, b) precipitate as carbonates generated from the dissociation of bicarbonate and c) metals which can only precipitate if there is free carbonate present in solution.
Keywords: Heavy metals -- Toxicology; Spirulina; Carbonic anhydrase; Algae -- Metabolism; Photosynthesis